Causes of death and survival analysis for patients with retinoblastoma in Jordan - Bilbeisi, Tharwa; Almasry, Razaq; Obeidat, Mariam; Mohammad, Mona; Jaradat, Imad; Halalsheh, Hadeel; Alni’mat, Ayat; Ahmad, Danah Kanj; Alsaket, Nour; Mehyar, Mustafa; Al-Nawaiseh, Ibrahim; Yousef, Yacoub A. (Frontiers in Medicine, 2023)
Purpose To analyze causes and prognostic factors for death among Retinoblastoma (Rb) patients treated at a single specialized tertiary cancer center in Jordan. Methods We reviewed the mortality causes for all Rb patients who have been treated at the King Hussein Cancer Center between 2003 and 2019 and were followed for at least 3 years after diagnosis. The main outcome measures included demographics, laterality, tumor stage, treatment modalities, metastasis, survival, and causes of death. Results Twenty-four (5%) of the 478 patients died from retinoblastoma and 5-year survival was 94%. The mean age at diagnosis was 15 months (median, 18 months; range, 4–38 months); eight (33%) received diagnoses within the first year of life. Eleven (46%) were boys, 16 (67%) had bilateral disease, and 3 (13%) had a positive family history. The stage for the worst eye was C for 1 (4%) patient, D in 6 (25%) patients, and E (T3) in 15 (63%) patients. Two patients had extraocular Rb at diagnosis, and four of the patients who had intraocular Rb at diagnosis refused treatment and then came back with extraocular Rb. In total, extraocular disease was encountered in six eyes (six patients). After a 120-month median follow-up period, 24 patients (5%) died of second neoplasms (n = 3) or metastases (n = 21). Significant predictive factors for metastasis and death included advanced IIRC tumor stage (p < 0.0001), the presence of high-risk pathological features in the enucleated eyes (p = 0.013), parental refusal of the recommended primary treatment plan (p < 0.0001), and extraocular extension (p < 0.0001). Conclusion The 5-year survival rates of Rb patients in Jordan are as high as those in high-income countries. However, 5% are still dying from metastatic disease, prompting the need for awareness campaigns to educate the public about the high cure rates and to prevent treatment abandonment.